Decision Supporting System For Providing Free Accommodation To Foreign Tourists In North Sumatera Using Smart Method - Raja Bimantara Wijaya Sitepu; Darjat Saripurna; Mili Arfisyari (CV. AFDIFAL MAJU BERKAH, 2022)
A program for providing free accommodation to foreign tourists in North Sumatra has been designed using the SMART method. This program uses a system that functions as a ranking. This program uses a ranking system that aims to select on desktop devices such as computers and laptops to be carried out in a systematic assessment of the person concerned, this program uses the MySQL system to do programming, this program is intended for agencies whose function is to select foreign tourists. The Program for Providing Free Accommodation to Foreign Tourists in Sumatra uses XAMPP which can be quite easy to use, with this program it can help and facilitate several educational institutions who want to provide free accommodation in exchange for promotional services as well as teaching at their institutions.